2008
DOI: 10.1088/1751-8113/41/11/115303
|View full text |Cite
|
Sign up to set email alerts
|

An analytical relation between entropy production and quantum Lyapunov exponents for Gaussian bipartite systems

Abstract: Abstract. We study and compare the information loss of a large class of Gaussian bipartite systems. It includes the usual Caldeira-Leggett type model as well as Anosov models (parametric oscillators, the inverted oscillator environment, etc), which exhibit instability, one of the most important characteristics of chaotic systems. We establish a rigorous connection between the quantum Lyapunov exponents and coherence loss and show that in the case of unstable environments, coherence loss is completely determine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…preferred factorization into a degree of freedom and an environment is given, but note that we explicitly find that the entanglement entropy growth rate grows as the sum of the positive Lyapunov exponents, not just as the largest one. The original work of Zurek and Paz [6] had only one such positive exponent, and similarly with [12,18], though other studies have also found growth rates equal to the full sum [7,9]. We are also consistent with other earlier studies of entanglement entropy growth, but distinguished from them in that our system is not coupled to an external environment [6-8, 10, 14, 19, 21], our results are not perturbative [13] or numerical [34,35] and we do not work with a finite-dimensional Hilbert space [9,11] or invoke a random matrix or semi-classical approximation [15-17, 20, 36].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…preferred factorization into a degree of freedom and an environment is given, but note that we explicitly find that the entanglement entropy growth rate grows as the sum of the positive Lyapunov exponents, not just as the largest one. The original work of Zurek and Paz [6] had only one such positive exponent, and similarly with [12,18], though other studies have also found growth rates equal to the full sum [7,9]. We are also consistent with other earlier studies of entanglement entropy growth, but distinguished from them in that our system is not coupled to an external environment [6-8, 10, 14, 19, 21], our results are not perturbative [13] or numerical [34,35] and we do not work with a finite-dimensional Hilbert space [9,11] or invoke a random matrix or semi-classical approximation [15-17, 20, 36].…”
Section: Introductionmentioning
confidence: 95%
“…This is done for a closed system, and we will study the dependence on the choice of coarse-graining and initial state. The idea is to study the quantum counterparts of closed Hamiltonian chaotic dynamical systems with finitely many degrees of freedom, similarly to previous studies of closed systems in the quantum chaos and decoherence literature [9,12,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors conjectured that in a system coupled to an environment, the rate of entropy growth is equal to the sum of the positive Lyapunov exponents, the classical Kolmogorov-Sinai entropy rate [8][9][10]. A large body of numerical and analytical studies during the early 2000 [11][12][13][14][15][16][17][18][19][20][21][22][23][24] proved consistent with the Zurek-Paz surmise, and suggested further relationships between semiclassical entanglement dynamics and the chaoticity of the underlying trajectories. Related work focused on understanding the emergence of quantum irreversibility and decoherence through the dynamics of the purity and the Loschmidt echo [25,26].…”
Section: Introductionmentioning
confidence: 95%
“…( 44), this increase may be visualized as an enhancement of the projected volume spanned by the reduced quantum fluctuations within the subsystem's phase space, due to the progressive stretching of the global phase-space volume spanned by the quantum fluctuations. Similarly, the von Neumann entanglement entropy (19) can be computed as…”
Section: Semiclassical Entanglement Entropiesmentioning
confidence: 99%